Some properties of a class of holomorphic functions associated with tangent function - Khan Muhammad Ghaffar; Mashwani Wali Khan; Salleh Zabidin; Tchier Fairouz; Khan Bilal; Malik Sarfraz Nawaz (Demonstratio Mathematica, 2024)
In this study, we define new class of holomorphic functions associated with tangent function. Furthermore, we examine the differential subordination implementation results related to Janowski and tangent functions. Also, we investigate some extreme point theorem and partial sums results, necessary and sufficient conditions, convex combination, closure theorem, growth and distortion bounds, and radii of close-to-starlikeness and starlikeness for this newly defined functions class of holomorphic functions.